(untitled) - Falk, Randee (New York, 1993)
Contents: The American people; New England; New York; ThMid-Atlantic Region; The South; The Midwest; The Southwest; The Rocky Mountain Region; The Pacific Northwest and Alaska; California and Hawaii.
Keywords: Civilization,Geography; United States,United States